Response Time Of Code Stroke Officers In The Management Of Ischemic Stroke Patients: Systematic Review - Kasiyanti, Heny; Mendrofa, Fery Agusman Motuho; Pujianto, Tri Ismu (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Stroke causes disability according to the American Heart Association (AHA) 87% of stroke patients experience disability and 77% experience complications. The highest prevalence of stroke is ischemic stroke where the standard therapy is to provide intravenous thrombolysis to patients with onset ≤ 4.5 hours. Response time of code stroke officers in the emergency area and fast activation will reduce disability and death rates. Researchers conducted a literature study and passive observation. This research design uses a cross study. In this systematic review, the research article uses the RCT research method and studies method with data analysis using meta-analysis. From a journal literature search using two databases, namely Science direct as many as N = 4 journal articles and Google Scholar as many as N = 3 articles, so that a total of N = 7 journal articles of literature by conducting an advanced search with keywords: response time, code stroke, with the addition of And, OR, published journals 5 years (2019 - 2024), in the form of complete journal articles, scholarly journals and journal articles in Indonesian and English. The findings of the article show that the response time of stroke code officers in the management of stroke patients in the emergency unit greatly affects the quality of life and risk of disability / disability of patients.